Effect of Tax Avoidance on the Financial Performance of Manufacturing Companies Listed on the IDX - Andi Hermanto; Mukhibi Anwar Sholih; Elli Sulistyaningsih (CV. Ulil Albab Corp, 2025)
This study aims to analyze the effect of tax avoidance on the financial performance of manufacturing companies, which is the objective of this article from 2019 to 2023. The independent variable, tax avoidance, is proxied by ETR, while the dependent variable, financial performance, is proxied by ROA. The analysis was conducted using a quantitative approach using panel data regression methods and a model selection test, where the test results determined the Fixed Effect Model as the best model. The regression results indicate that tax avoidance has a negative effect on financial performance, but is not partially significant. Conversely, the simultaneous test (F-test) shows that the model is significant overall. The Adjusted R² value of 93.5% indicates that the variability in financial performance can be largely explained by the model. Conceptually, these findings support agency theory, which asserts that tax avoidance practices negatively impact company performance. These findings are expected to contribute to management in formulating more optimal tax strategies and to regulators in developing responsive tax policies.